Exploring Interfaith Marriage in Qur’ān: A Hermeneutic and Anthropological Analysis of Permissibility - Safrodin; Anila Umriana; Fihris; Nasikhin (Journal of Islamic Thought and Civilization, 2024)
This study seeks to explain the concept of the permissibility of interfaith marriage, as found in the interpretation of Surah Al-Maidah: 05, within the cultural context of Arabic society. It explores  cultural systems, which influenced the socio-anthropological understanding of this permissibility. The research employs a qualitative approach, utilizing muqaran (comparative) and hermeneutic interpretation methods alongside an anthropological perspective. This study demonstrated several key findings on interfaith marriage in Al-Maidah: 05. The verse conceptually permits Muslim men to marry women from Ahl al-Kitab (People of the Book) under certain conditions, according to various scholarly interpretations. The text also indicates that Muslim men may marry women from Ahl al-Kitab who are independent and able to preserve their honor (muhsanat), provided they pay the dowry. Some scholars assert this permissibility applies without restriction, while others limit it to Ahl al-Kitab before Islam or to Ahl al-Kitab Dzimmiyyah, excluding Jews and Christians in some interpretations. The permissibility of such marriages from a socio-anthropological perspective reflects a continuation of earlier interfaith marriage practices among Arabs, influenced by the patriarchal social system, which was later redefined according to the Islamic perspective . Thus, the concept of interfaith marriage in Al-Maidah: 05 is deeply rooted in both pre-Islamic cultural practices and evolving Islamic jurisprudence, indicating that interfaith marriage conception has Quranic relevance.